2006
DOI: 10.1086/498931
|View full text |Cite
|
Sign up to set email alerts
|

Large Proper Motions in the Jet of the High‐Mass YSO Cepheus A HW2

Abstract: Using high angular resolution ($0B25-0B05) Very Large Array (VLA) observations made at 3.6 cm, 1.3 cm, and 7 mm during the period 1991-2004, we report the detection of large proper motions in the components of the radio continuum jet associated with the high-mass young stellar object (YSO) HW2 in the star-forming region Cepheus A. The relative proper motions observed for the two main components of the outflow, moving away from the central source in nearly opposite directions, are of the order of 140 mas yr À1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
194
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(219 citation statements)
references
References 37 publications
24
194
0
1
Order By: Relevance
“…This would be about 100 times brighter than typical low-mass protostars at that distance. Also associated with HW2 is a "biconical thermal radio jet" at the size scale of ≃1 ′′ (≃725 AU), with the ionized gas exhibiting proper motions with velocities ≥ 500 km s −1 along the axis of the jet 14,19,20 . In addition, we estimate that the luminosity of the masers associated with Table 1.…”
Section: -2 -mentioning
confidence: 99%
“…This would be about 100 times brighter than typical low-mass protostars at that distance. Also associated with HW2 is a "biconical thermal radio jet" at the size scale of ≃1 ′′ (≃725 AU), with the ionized gas exhibiting proper motions with velocities ≥ 500 km s −1 along the axis of the jet 14,19,20 . In addition, we estimate that the luminosity of the masers associated with Table 1.…”
Section: -2 -mentioning
confidence: 99%
“…The gas shows signs of rotation and is perpendicular to the highvelocity outflow (∼500 km s −1 ) seen in the radio continuum (Curiel et al 2006). The molecular outflow that we observe in methanol is blueshifted to the NE, which implies that this side of the outflow is pointing towards the observer, Fig.…”
Section: Outflow Morphologymentioning
confidence: 52%
“…The object shows both large-scale molecular outflows over ∼1 (Gómez et al 1999) and signs of collapse over a similar extent (Bottinelli & Williams 2004;Sun & Gao 2009). At the core of HW2, a thermal jet extends over ∼2 and proper motion outflow velocities of ∼500 km s −1 have been measured in the radio (Hughes & Wouterloot 1984;Curiel et al 2006). Although a superposition of gas components at different positions cannot be completely ruled out (Brogan et al 2007;Comito et al 2007), the evidence is building that there is a disk at the centre of the jet, which is observable in both molecular gas and dust (Patel et al 2005;Torrelles et al 2007;Jiménez-Serra et al 2007), as argued in detail in Jiménez-Serra et al (2009).…”
Section: Introductionmentioning
confidence: 83%
“…This source is usually refered to as the center of the Cep A region. A thermal radio-jet with a position angle of ∼45 • is present (Curiel et al 2006), indicated by arrows in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Garay et al (1996) proposed that HW 3d drives an outflow directed towards HW 7, which is interpreted as shock induced radio emission. From their proper motion measurements of the individual components of HW 7, Curiel et al (2006) propose that the driving source is located just north of the HW 7a component, mainly because HW 7a moves almost perpendicularly to the rest of the HW 7 sources due south. We identify this source with GPFW 2 (Goetz et al 1998).…”
Section: Introductionmentioning
confidence: 99%